PANTANG LARANG DALAM MASYARAKAT MELAYU KECAMATAN SEKADAU HILIR KABUPATEN SEKADAU - Hadi, Tri Utomo; Saman, Sisilya; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study with regard to the field of sociolinguistics. The problems addressed in this study is the abstinence forbids inventory, classification and function taboo Sekadau Malay community. The purpose of this study was to describe taboo based research problem. This research uses descriptive method with qualitative terms and entholinguistic approach. Sources of data in this research taboo language Malay society Sekadau told by informants in Sungai Ringin and Village Mungguk. The data collection technique used was direct observation method capable and methods refer to. Data collection tool is a questionnaire, data card and a recorder. Based on data analysis there were 35 of taboo Sekadau Malay society. Taboo classified with 5 classification. Based on the salvation of souls there are 14 taboos, based on the work as much as 3 taboos, by the female gender, there were 7 taboos and based sex male there are 2 taboos based on where there are three taboos, and by the time as much as 6 taboos. The function of taboo Sekadau Malay society is as a teaching and counsel to explain the function of the classification of taboo Sekadau Malay community.Â Keywords: Taboo, Malay Sekadau, Sociolinguistics